Additional chemical polymerization of dual resin cements: reality or a goal to be achieved? - Umetsubo, Luzia Sakaguti; Yui, Karen Cristina Kazue; Borges, Alessandra Bühler; Barcellos, Daphne Camara; GonÇalves, Sérgio Eduardo De Paiva (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
AbstractIntroduction This study serves as a warning to dentists and researchers that dual-cured resin cements may not polymerize completely under some prosthetic crowns.Objective The aim of this study was to analyse the polymerization degree of dual-cured resin cements under prosthetic barrier, by microhardness test.Material and method Three cements (Bistite II, RelyX ARC and Variolink II) were light-cured through different barriers, placed between the cement and the light source: G1: without barrier; G2: composite resin (Cesead); G3: Inceram alumina; G4: IPS Empress; G5: Inceram zirconia; G6: tooth fragment. Photopolymerization was carried out using a halogen light unit (650 mW/cm2); microhardness was evaluated using the Microhardness Tester FM 700, under a load of 50gf with a dwell time of 15s, at two evaluation times (30min and 24h).Result The results were submitted to ANOVA and Tukey tests (5%). Both Inceram alumina and Inceram zirconia ceramic barriers hindered polymerization. Bistite, followed by RelyX and Variolink, exhibited the highest microhardness values (p<0.05). As the highest values were obtained without a barrier, it was determined that the barrier, followed by the tooth, influenced microhardness. Both Empress and Cesead had the smallest microhardness values but with no statistically significant difference between them.Conclusion The barrier negatively affected the microhardness of dual-cured resin cements; evaluation time did not affect microhardness values for most of the conditions tested. There is a limited effect of the chemical activator on the polymerization of some dual-cured cements, and their performance is product specific.

ResumoIntrodução Este trabalho serve como um alerta para dentistas e pesquisadores, que alguns cimentos resinosos duais podem não polimerizar completamente sob alguns tipos de coroas protéticas.Objetivo Analisar o grau de polimerização de cimentos resinos duais, sob barreiras protéticas, por teste de microdureza.Material e método Três cimentos: Bistite II, RelyX ARC e Variolink II, foram fotopolimerizados através da interposição de vários tipos de barreiras, interpostas entre o cimento e a fonte de luz, formando os grupos: G1: sem barreira; G2: Resina composta Cesead; G3: Inceram alumina/Allceram; G4: IPS Empress; G5: Inceram zircônia/Allceram; G6: fragmento dental. Utilizou-se a luz halógena (650 mW/cm2) para fotoativação e a microdureza foi avaliada: 50gf durante 15s (MicrohardnessTester FM 700), em dois períodos (30min e 24h) pós ativação. Os dados foram submetidos à ANOVA e teste de Tukey (5%). As interposições de Inceram alumina e Inceram zircônia resultaram na polimerização deficiente dos cimentos, impossibilitando a realização dos ensaios.Resultado Para o fator cimento, o Bistite revelou a maior microdureza, seguido do RelyX e do Variolink (p<0,05). A barreira influenciou a microdureza, sendo que os maiores valores foram obtidos sem barreira, seguida do dente. Empress e Cesead proporcionaram os menores valores de microdureza e não diferiram entre si.Conclusão A barreira afetou negativamente a microdureza dos cimentos resinosos duais; o período de avaliação não afetou os valores de microdureza para quase todas as condições testadas; existe um fator limitante do ativador químico na polimerização de alguns cimentos resinosos duais, e seu desempenho é dependente do produto.
Polimerização química adicional de cimentos resinosos duais: realidade ou um objetivo a ser atingido?
Keywords: Dental cements; microhardness; cementation; polymerization; Cimentos dentários; microdureza; cimentação; polimerização